Economic Recovery, Consolidation, and Sustainable Growth Proceedings of the 6th International Scientific Conference on Business and Economics (ISCBE), North Macedonia, May 2023 - Bexheti, Abdylmenaf; Abazi-Alili, Hyrije; Dana, Léo-Paul; Ramadani, Veland; Caputo, Andrea (Springer Proceedings in Business and Economics, 2023)
XXI, 847 p. 139 illus., 107 illus. in color.